Active materials and fluoride ion batteries

By providing new active substances with infinite layer structure and specific elements, the problem of insufficient performance of active substances in existing fluoride ion batteries is solved, and the battery capacity and circulation characteristics are improved, and resource risks are reduced.

CN115084496BActive Publication Date: 2025-05-02TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210219868.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-29
Filing Date
2022-03-08
Publication Date
2025-05-02
Estimated Expiration
2042-03-08

AI Technical Summary

Technical Problem

The active substance performance of existing fluoride ion batteries is insufficient, making it difficult to improve the overall performance of the battery.

Method used

A novel active substance has an infinite layer structure and a specific crystalline phase composed of alkaline earth metal elements, transition metal elements and oxygen, preferably represented by ApBqOr, and has a peak at a specific position in CuKα ray X-ray diffraction assay.

Benefits of technology

By using this new active substance, the capacity and circulation characteristics of fluoride ion batteries are significantly improved, expansion and contraction caused by changes in crystal structure are avoided, and resource risks are low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115084496B_ABST
    Figure CN115084496B_ABST
Patent Text Reader

Abstract

The present invention relates to an active material and a fluoride ion battery. The main object of the present disclosure is to provide a novel active material that can be used in a fluoride ion battery. In the present disclosure, the above-mentioned problem is solved by providing an active material, wherein the active material is an active material for a fluoride ion battery and has an infinite layer structure and is composed of A p B q O r represents a crystalline phase, where A is at least one of an alkaline earth metal element and a rare earth element, B is a transition metal element, p satisfies 0.8 ≤ p ≤ 1, q satisfies 0.8 ≤ q ≤ 1, and r satisfies 1.5 ≤ r ≤ 2.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to active materials and fluoride ion batteries. Background Art

[0002] As a high voltage and high energy density battery, for example, a Li ion battery is known. A Li ion battery is a cation-based battery using Li ions as carriers. On the other hand, as an anion-based battery, a fluoride ion battery using fluoride ions as carriers is known.

[0003] For example, Patent Document 1 discloses, as an active material for a fluoride ion battery, an active material having a crystalline phase having a layered perovskite structure.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-143044 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In order to improve the performance of fluoride ion batteries, new active materials are needed. The present disclosure is completed in view of the above actual situation, and the main purpose is to provide a new active material that can be used in fluoride ion batteries.

[0009] Means for solving problems

[0010] In order to solve the above problems, the present disclosure provides an active material for a fluoride ion battery, which has an infinite layer structure and is composed of A p B q O r (A is at least one of an alkaline earth metal element and a rare earth element, B is a transition metal element, p satisfies 0.8≤p≤1, q satisfies 0.8≤q≤1, and r satisfies 1.5≤r≤2.5) a crystalline phase represented by.

[0011] According to the present disclosure, it has been newly discovered that an active material having a crystal phase with an infinite layer structure and a specific composition functions as an active material for a fluoride ion battery.

[0012] In the above disclosure, the ratio of the above p to the above q (p / q) may be 1.

[0013] In the above disclosure, the ratio of the above p to the above q (p / q) may be less than 1.

[0014] In addition, the present disclosure provides an active material, which is an active material for a fluoride ion battery, having an infinite layer structure and a crystalline phase containing A (A is at least one of an alkaline earth metal element and a rare earth element), B (B is a transition metal element) and O, wherein the above-mentioned crystalline phase has peaks at 2θ=32.1°±1.0°, 2θ=35.1°±1.0°, 2θ=46.0°±1.0° and 2θ=59.1°±1.0° in X-ray diffraction measurement using CuKα rays.

[0015] According to the present disclosure, it has been newly discovered that an active material having an infinite layer structure and a crystal phase having an XRD peak at a predetermined position functions as an active material for a fluoride ion battery.

[0016] In addition, the present disclosure provides an active material, which is an active material for a fluoride ion battery, having an infinite layer structure and a crystalline phase containing A (A is at least one of an alkaline earth metal element and a rare earth element), B (B is a transition metal element) and O, wherein the above-mentioned crystalline phase has peaks at 2θ=32.9°±1.0°, 2θ=36.0°±1.0°, 2θ=43.6°±1.0° and 2θ=56.4°±1.0° in X-ray diffraction measurement using CuKα rays.

[0017] According to the present disclosure, it has been newly discovered that an active material having an infinite layer structure and a crystal phase having an XRD peak at a predetermined position functions as an active material for a fluoride ion battery.

[0018] In the above disclosure, the above A may be at least one of Ca, Sr, Ba, La and Ce.

[0019] In the above disclosure, the above B may be at least one of Fe, Ni and Cu.

[0020] In the above disclosure, the above B may be Fe.

[0021] In the above disclosure, the above crystalline phase can be composed of Ca x Sr 1-x It is represented by FeO2 (x satisfies 0<x<1).

[0022] In the above disclosure, the above x may satisfy 0.6≤x<1.

[0023] In the above disclosure, the above crystalline phase can be composed of Ca p CuO2 (p satisfies 0.8≤p<1).

[0024] In addition, the present disclosure provides a fluoride ion battery, which is a fluoride ion battery having a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and an electrolyte layer formed between the above-mentioned positive electrode layer and the above-mentioned negative electrode layer, wherein the above-mentioned positive electrode active material or the above-mentioned negative electrode active material is the above-mentioned active material.

[0025] According to the present disclosure, a fluoride ion battery having a good capacity can be obtained by using the above-mentioned active material.

[0026] Effects of the Invention

[0027] The present disclosure exerts an effect of being able to provide a novel active material that can be used in a fluoride ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is an explanatory diagram for explaining the infinite layer structure in the present disclosure.

[0029] Figure 2 This is a schematic cross-sectional view showing an example of an all-solid-state battery in the present disclosure.

[0030] Figure 3 It is a schematic cross-sectional view showing the structure of the battery produced in Examples 1 to 6 and Comparative Examples 1 and 2.

[0031] Figure 4 The following are the results of XRD measurement of Examples 1 to 6 and Comparative Example 1.

[0032] Figure 5 It is a graph showing the results of the charge and discharge tests of Examples 1 to 6 and Comparative Examples 1 and 2.

[0033] Figure 6 This is a graph comparing the discharge capacities obtained in Examples 1 to 6 with the theoretical capacity.

[0034] Figure 7 These are the results of XRD measurements of Examples 7 and 8.

[0035] Figure 8 It is a graph showing the results of the charge and discharge tests of Example 7 and Example 8.

[0036] Description of Reference Numerals

[0037] 1. Positive electrode layer

[0038] 2 Negative electrode layer

[0039] 3 Electrolyte layer

[0040] 4. Positive electrode collector

[0041] 5 Negative electrode collector

[0042] 6 Battery housing

[0043] 10 Fluoride Ion Battery DETAILED DESCRIPTION

[0044] Hereinafter, the active material and the fluoride ion battery in the present disclosure will be described in detail.

[0045] A. Active substances

[0046] The active material in the present disclosure has a crystalline phase having an infinite layer structure and containing A (A is at least one of an alkaline earth metal element and a rare earth element), B (B is a transition metal element), and O. The crystalline phase is preferably composed of A p B q O r (A and B are as described above, p satisfies 0.8≤p≤1, q satisfies 0.8≤q≤1, and r satisfies 1.5≤r≤2.5) In addition, the above-mentioned crystalline phase preferably has a peak at a predetermined position in X-ray diffraction measurement using CuKα rays.

[0047] According to the present disclosure, it is newly discovered that an active material having a specified crystalline phase functions as an active material of a fluoride ion battery. In addition, the active material in the present disclosure has the advantage of good capacity. In addition, the active material in the present disclosure can suppress the expansion and contraction of the active material with the change of the crystal structure, so the cycle characteristics and rate characteristics are excellent. Furthermore, for example, when the crystalline phase in the present disclosure contains alkaline earth metal elements, transition metal elements and O elements as constituent elements, it also has the advantage of low resource risk.

[0048] As described above, it is known that an active material having a crystalline phase with a layered perovskite structure (also referred to as a layered perovskite oxide) can be used in a fluoride ion battery. The layered perovskite oxide can be charged and discharged by the intercalation reaction of fluoride ions into the interlayer, so the expansion and contraction of the active material with the change of the crystal structure can be suppressed. Therefore, the battery using the layered perovskite oxide becomes a battery with excellent cycle characteristics and rate characteristics. On the other hand, in the layered perovskite oxide, the skeleton for accommodating fluoride ions becomes larger and the theoretical capacity becomes smaller.

[0049] On the other hand, the present inventors have found that an active material having a crystal phase having an infinite layer structure and containing a specific element as described later can be used in a fluoride ion battery and has a good capacity.

[0050] Here, an example of the infinite layer structure of the crystal phase in the present disclosure will be described in more detail using the drawings. Figure 1 (a) shows an example of an infinite layer structure of a crystalline phase represented by SrFeO2, Figure 1(b) shows an example of an infinite layer structure of a crystalline phase represented by CaFeO2. Figure 1 (c) shows an example of a perovskite structure represented by ABO3. Figure 1 Sr and Ca in (a) and (b) are equivalent to Figure 1 In (c), the A ion, Fe, is equivalent to the B ion. Figure 1 As shown in (a) to (c), the infinite layer structure is a structure in which the O element is selectively missing in the perovskite structure, and has an anion defect site. It is believed that for the active material in the present disclosure, due to the anion defect site, fluoride ions are more easily inserted and a diffusion path for fluoride ions is formed.

[0051] In addition, if Figure 1 As shown in (a) and (b), the infinite layer structure has different configurations of elements due to the difference in A ions. Figure 1 In (a), the A ion is Sr, forming a planar four-coordinate structure. Figure 1 In (b), the A ion is Ca, forming a coordination state in which a planar four-coordinate structure is deformed into a tetrahedral structure. This is believed to be caused by the difference in ionic radius between Sr and Ca. In this way, it is believed that the active material in the present disclosure has good capacity characteristics compared with perovskite oxides, depending on the presence or absence of anion defect sites and the configuration of elements. It should be noted that the infinite layer structure can be identified, for example, by X-ray diffraction measurement (XRD measurement).

[0052] The crystalline phase of the active material in the present disclosure is preferably composed of A p B q O r (A is at least one of an alkaline earth metal element and a rare earth element, B is a transition metal element, p satisfies 0.8≤p≤1, q satisfies 0.8≤q≤1, and r satisfies 1.5≤r≤2.5).

[0053] A is at least one of an alkaline earth metal element and a rare earth element. A may be only an alkaline earth metal element, only a rare earth element, or both an alkaline earth metal element and a rare earth element. In addition, A may be one element belonging to the alkaline earth metal element or the rare earth element, two elements belonging to the alkaline earth metal element or the rare earth element, or three or more elements belonging to the alkaline earth metal element or the rare earth element.

[0054] Examples of alkaline earth metal elements include Be, Mg, Ca, Sr, Ba, and Ra. On the other hand, examples of rare earth elements include lanthanoid elements such as La and Ce, Sc, and Y. Among them, A is preferably at least one of Ca, Sr, Ba, La, and Ce.

[0055] In particular, A is preferably at least one of Ca, Sr and Ba, and may be two or more. The ionic radius of these elements is small, and it is not easy to become an obstacle when the fluoride ions are inserted into the active material. In addition, A is more preferably at least one of Ca and Sr, and particularly preferably at least Ca. Since the atomic weight of Ca and Sr, especially Ca, is small, the capacity per 1g of active material becomes larger. In addition, A can be at least one of La and Ce.

[0056] B is a transition metal element. In addition, B can be one element belonging to the transition metal element, two elements belonging to the transition metal element, or more than three elements belonging to the transition metal element. As the transition metal element, for example, Fe, Ni, Cu, Co, Mn, etc. can be listed.

[0057] In A p B q O r In the above, p satisfies 0.8≤p≤1, q satisfies 0.8≤q≤1, and r satisfies 1.5≤r≤2.5. p can be 1 or less than 1. In the latter case, p can be less than 0.98, less than 0.95, or less than 0.9. Similarly, q can be 1 or less than 1. In the latter case, q can be less than 0.98, less than 0.95, or less than 0.9. In addition, r can be 2, less than 2, or greater than 2. In the present disclosure, p=1, q=1, and r=2. In addition, in the present disclosure, 0.8≤q≤1, q=1, and r=2.

[0058] The active material in the present disclosure has a crystalline phase consisting of A p B q O r In the case of Bb containing Fe, there is more room for the transition metal element of B to be oxidized and reduced during the insertion and extraction of fluoride ions. Therefore, it is believed that more fluoride ions can be inserted into the active material. For example, in the case where Bb contains Fe, since Fe can exist in a divalent state, there is more room for Fe to be oxidized and reduced during the insertion and extraction of fluoride ions, and it is believed that more fluoride ions can be inserted into the active material. As a result, it is believed that the capacity becomes good. In this way, B preferably contains a divalent transition metal element as the main component. "Main component" refers to the largest molar ratio. It should be noted that when Fe is used as the B ion in the perovskite structure (ABO3), Fe usually exists in a tetravalent state. Therefore, Fe (tetravalent) in the perovskite structure has less room for oxidation and reduction than Fe (divalent) in the infinite layer structure.

[0059] In addition, the above-mentioned crystalline phase is preferably composed of Ca x Sr 1-xFeO2 (x satisfies 0<x<1). x can be greater than 0.4, greater than 0.6, greater than 0.7, or greater than 0.8. In addition, x can be less than 0.95, or less than 0.9. Here, it is considered that since the atomic weight of Ca is smaller than that of Sr, the capacity of the composition that generally does not contain Sr (x=1) is large. In contrast, as described in the embodiments described later, in a composition containing Sr in a specified ratio (0.6≤x<1), an active material showing a capacity equal to or greater than that of a composition that does not contain Sr (x=1) is obtained. The reason for this is not clear, but it is speculated as follows. First, in the above composition, it is speculated that CaFeO2 and SrFeO2 coexist. As mentioned above, both have infinite layer structures, but the spatial arrangements of the elements are different (refer to Figure 1 ). Therefore, it is presumed that the coexistence of CaFeO2 and SrFeO2 in a predetermined ratio in the crystal phase produces a deformation that facilitates the insertion of fluoride ions into the active material.

[0060] In addition, the above-mentioned crystalline phase is preferably composed of La p NiO2 (p satisfies 0.8≤p≤1). In addition, the above-mentioned crystalline phase is preferably composed of Ca p CuO2 (p satisfies 0.8≤p≤1). In these compositions, p may be 1 or less than 1. In the latter case, p may be less than 0.98, less than 0.95, or less than 0.9.

[0061] In by A p B q O r In the above-mentioned crystalline phase represented by, the ratio of p to q (p / q) can be 1 or less than 1. The former is equivalent to a crystalline phase without defects at the A site, referred to as crystalline phase α in the present disclosure. The latter is equivalent to a crystalline phase with defects at the A site, referred to as crystalline phase β in the present disclosure. In crystalline phase β, p / q can be less than 0.98, less than 0.95, or less than 0.9. On the other hand, p / q is, for example, more than 0.8.

[0062] The crystalline phase α preferably has peaks at 2θ=32.1°±1.0°, 2θ=35.1°±1.0°, 2θ=46.0°±1.0° and 2θ=59.1°±1.0° in X-ray diffraction measurement using CuKα rays. These peak positions may deviate within the range of ±0.5° or within the range of ±0.3°.

[0063] Crystalline phase β is a crystalline phase in which defects are generated at the A site in the crystalline phase α. It is speculated that the crystal structure of the crystalline phase β is deformed compared to the crystalline phase α while maintaining an infinite layer structure. The inventors found that by deforming the crystal structure, a higher capacity active material was obtained. Crystalline phase β preferably has peaks at 2θ=32.9°±1.0°, 2θ=36.0°±1.0°, 2θ=43.6°±1.0° and 2θ=56.4°±1.0° in an X-ray diffraction measurement using CuKα rays. These peak positions can deviate back and forth within the range of ±0.5°, or they can deviate back and forth within the range of ±0.3°.

[0064] Crystal phase α and crystal phase β may have different space groups even if their compositions are similar. For example, the space group of CaCuO2 is P4 / mmm, and the space group of Ca 1-x The space group of CuO2 (x>0) is Fmmm.

[0065] The active material in the present disclosure may be a single-phase material having only the crystalline phase in the present disclosure described above, or may be a multiphase material having the crystalline phase in the present disclosure and other crystalline phases. In the latter case, it is preferred to have the crystalline phase in the present disclosure as the main phase. "Main phase" refers to the crystalline phase to which the peak with the largest intensity in the XRD diagram belongs. In the case where the active material has the crystalline phase in the present disclosure as the main phase, the ratio of the crystalline phase in the present disclosure to all crystalline phases is, for example, 50% by weight or more, 70% by weight or more, 90% by weight or more, or 99% by weight or more. It should be noted that as other crystalline phases, for example, crystalline phases having a perovskite structure can be listed.

[0066] The composition (overall composition) of the active material in the present disclosure is not particularly limited, and is preferably composed of A P B Q O R (A is at least one of an alkaline earth metal element and a rare earth element, B is a transition metal element, P satisfies 0.8≤P≤1, Q satisfies 0.8≤Q≤1, and R satisfies 1.5≤R≤2.5).

[0067] The shape of the active material is not particularly limited, and may be, for example, a particle shape. 50 ) is, for example, 1 nm or more, and may be 10 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 100 μm or less, and may be 30 μm or less. The average particle size (D 50 ) can be calculated, for example, by using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM). In addition, the active material in the present disclosure is generally used in a fluoride ion battery. The fluoride ion battery will be described later.

[0068] The method for producing the active material in the present disclosure is not particularly limited as long as it is a method that can obtain the target active material. For example, the active material having a crystalline phase α can be produced by reducing a precursor produced by a solid phase reaction method using a reducing agent. Specifically, a raw material composition containing A (A is at least one of an alkaline earth metal element and a rare earth element), B (B is a transition metal element) and O is heat-treated to produce a raw material composed of ABO by a solid phase reaction. y (y is greater than 2, such as AFeO3). The obtained precursor is sintered in a closed space together with a reducing agent such as CaH2 to reduce the precursor and obtain an active material having a crystalline phase α. The conditions such as the sintering temperature and the sintering time can be adjusted appropriately. In addition, the precursor can also be obtained by reacting the raw material composition in molten KOH.

[0069] In addition, an active material having a crystalline phase β can be obtained, for example, by subjecting a raw material composition containing A (A is at least one of an alkaline earth metal element and a rare earth element), B (B is a transition metal element) and O to one or more heat treatments in an oxygen atmosphere. Conditions such as the firing temperature, firing time and number of heat treatments can be appropriately adjusted.

[0070] B. Fluoride ion battery

[0071] Figure 2 This is a schematic cross-sectional view showing an example of a fluoride ion battery in the present disclosure. Figure 2 The fluoride ion battery 10 shown has a positive electrode layer 1 containing a positive electrode active material, a negative electrode layer 2 containing a negative electrode active material, an electrolyte layer 3 formed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 for collecting current from the positive electrode layer 1, a negative electrode collector 5 for collecting current from the negative electrode layer 2, and a battery case 6 for accommodating these components. In the present disclosure, the above-mentioned positive electrode active material or the above-mentioned negative electrode active material is the above-mentioned active material.

[0072] According to the present disclosure, by using the above-mentioned active material, a fluoride ion battery with good capacity can be obtained. In addition, by using the above-mentioned active material, a fluoride ion battery capable of avoiding resource risks can be obtained.

[0073] 1. Positive electrode layer

[0074] The positive electrode layer in the present disclosure is a layer containing at least a positive electrode active material. In addition, the positive electrode layer may contain at least one of an electrolyte, a conductive material, and a binder as necessary.

[0075] The positive electrode active material is preferably the active material in the present disclosure described above. When the negative electrode active material described later is the above active material, the positive electrode active material is preferably any active material having a higher potential.

[0076] As a conductive material, as long as it has the desired electronic conductivity, it is not particularly limited, for example, carbon materials can be listed. As a carbon material, for example, carbon black such as acetylene black, ketjen black, furnace black, thermal black, graphene, fullerene, and carbon nanotubes can be listed. On the other hand, as an adhesive, as long as it is a chemically stable and electrically stable adhesive, it is not particularly limited, for example, fluorine-based adhesives such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE) can be listed. About electrolyte, the same as the content described in "3. Electrolyte layer" described later.

[0077] The content of the positive electrode active material in the positive electrode layer is not particularly limited, and from the viewpoint of capacity, its content is preferably more. The content of the positive electrode active material is, for example, more than 30 weight %, more than 50 weight %, or more than 70 weight %. In addition, the thickness of the positive electrode layer is not particularly limited, and can be appropriately adjusted according to the constitution of the battery.

[0078] 2. Negative electrode layer

[0079] The negative electrode layer in the present disclosure is a layer containing at least a negative electrode active material. In addition, the negative electrode layer may contain at least one of an electrolyte, a conductive material, and a binder as necessary.

[0080] The negative electrode active material is preferably the active material in the present disclosure described above. When the positive electrode active material is the active material described above, the negative electrode active material is preferably any active material having a lower potential.

[0081] The electrolyte, conductive material and binder are the same as those described in the above-mentioned "1. Positive electrode layer", so the description here is omitted. There is no particular limitation on the content of the negative electrode active material in the negative electrode layer, and from the viewpoint of capacity, its content is preferably more. The content of the negative electrode active material is, for example, 30% by weight or more, 50% by weight or more, or 70% by weight or more. In addition, there is no particular limitation on the thickness of the negative electrode layer, and it can be appropriately adjusted according to the composition of the battery.

[0082] 3. Electrolyte layer

[0083] The electrolyte layer in the present disclosure is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least an electrolyte. In addition, the electrolyte layer may further contain an adhesive as required. Regarding the type of adhesive, it is the same as the content described in the above-mentioned "1. Positive electrode layer", so the description here is omitted. The electrolyte can be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0084] As the above-mentioned electrolyte, for example, an electrolyte containing a fluoride salt and an organic solvent can be listed. As the fluoride salt, for example, an inorganic fluoride salt, an organic fluoride salt, and an ionic liquid can be listed. As an example of an inorganic fluoride salt, for example, XF (X is Li, Na, K, Rb or Cs) can be listed. As an example of a cation of an organic fluoride salt, an alkylammonium cation such as a tetramethylammonium cation can be listed. The concentration of the fluoride salt in the electrolyte is, for example, not less than 0.1 mol% and not more than 40 mol%, and can be not less than 1 mol% and not more than 10 mol%.

[0085] The organic solvent of the electrolyte is usually a solvent that dissolves fluoride salts. As an organic solvent, for example, ethylene glycol dimethyl ether (glyme) such as triethylene glycol dimethyl ether (G3) and tetraethylene glycol dimethyl ether (G4) can be listed; cyclic carbonates such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), propylene carbonate (PC), and butylene carbonate (BC); chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). In addition, ionic liquids can also be used as organic solvents.

[0086] Examples of the solid electrolyte include inorganic solid electrolytes. Examples of the inorganic solid electrolyte include fluorides containing lanthanide elements such as La and Ce, fluorides containing alkali metal elements such as Li, Na, K, Rb, and Cs, and fluorides containing alkaline earth elements such as Ca, Sr, and Ba. Specifically, examples include fluorides containing La and Ba (e.g., La 0.9 Ba 0.1 F 2.9 ), a fluoride containing Pb and Sn. The thickness of the electrolyte layer is not particularly limited and can be appropriately adjusted according to the configuration of the battery.

[0087] 4. Other components

[0088] The fluoride ion battery in the present disclosure preferably has a positive electrode current collector for collecting current in the positive electrode layer, a negative electrode current collector for collecting current in the negative electrode layer, and a battery case for accommodating the above components. As the shape of the current collector, for example, a foil, a mesh, or a porous shape can be listed. In addition, the fluoride ion battery can have a separator between the positive electrode layer and the negative electrode layer. This is because a safer battery can be obtained. As the battery case, a conventionally known battery case can be used.

[0089] 5. Fluoride ion battery

[0090] The fluoride ion battery in the present disclosure may be a primary battery or a secondary battery, wherein a secondary battery is preferred. This is because it can be repeatedly charged and discharged, and is useful, for example, as a vehicle-mounted battery. It should be noted that a secondary battery also includes the use of a primary battery (the use for the purpose of only one discharge after charging). In addition, as the shape of the fluoride ion battery, for example, a coin type, a laminated type, a cylindrical type, and a square type can be listed.

[0091] It should be noted that the present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and technical solutions having substantially the same structure and exerting the same effects as the technical ideas described in the claims of the present disclosure are all included in the technical scope of the present disclosure.

[0092] Example

[0093] [Example 1]

[0094] (Synthesis of active substances)

[0095] The raw materials CaCO3 and Fe2O3 were weighed in a molar ratio of 2:1 and mixed using a ball mill. The obtained powder was pelletized and heat treated at 1200°C for 10 hours to obtain a precursor. The obtained precursor was pelletized and vacuum sealed in a glass tube together with particles of a reducing agent (CaH2). The glass tube was sintered at 300°C to synthesize an active material (CaFeO2).

[0096] (Battery production)

[0097] The obtained active material was used as the positive electrode active material and prepared as follows Figure 3 The battery shown in FIG. 1 (all-solid fluoride ion battery). The active material and the solid electrolyte (La 0.9 Ba 0.1 F 2.9 , fluoride ion conductive material) and conductive material (VGCF, electron conductive material) were weighed in a weight ratio of 30:60:10, mixed and pressed into tablets to obtain electrode tablets (10 mg). The obtained electrode tablets were used as working electrodes (positive electrodes). 0.9 Ba 0.1 F 2.9 A solid electrolyte layer (100 mg), a layer obtained by mixing PbSnF4 and acetylene black (AB), and a counter electrode (negative electrode) using a Pb foil were stacked and powder-pressed.

[0098] [Example 2]

[0099] An active material (SrFeO 2 ) and a battery were prepared in the same manner as in Example 1 except that SrCO 3 and Fe 2 O 3 as raw materials were weighed so as to have a molar ratio of 2:1.

[0100] [Example 3]

[0101] The active material (CaCO3, SrCO3 and Fe2O3) was prepared in the same manner as in Example 1 except that the raw materials were weighed in a molar ratio of 1.6:0.4:1. 0.8 Sr 0.2 FeO2) and batteries.

[0102] [Example 4]

[0103] The active material (CaCO3, SrCO3 and Fe2O3) was prepared in the same manner as in Example 1 except that the raw materials were weighed in a molar ratio of 1.2:0.8:1. 0.6 Sr 0.4 FeO2) and batteries.

[0104] [Example 5]

[0105] The active material (CaCO3, SrCO3 and Fe2O3) was prepared in the same manner as in Example 1 except that the raw materials were weighed in a molar ratio of 0.8:1.2:1. 0.4 Sr 0.6 FeO2) and batteries.

[0106] [Example 6]

[0107] The active material (CaCO3, SrCO3 and Fe2O3) was prepared in the same manner as in Example 1 except that the raw materials were weighed in a molar ratio of 0.4:1.6:1. 0.2 Sr 0.8 FeO2) and batteries.

[0108] [Comparative Example 1]

[0109] An active material (SrFeO 3 ) and a battery were produced in the same manner as in Example 2, except that calcination with the reducing agent (CaH 2 ) was not performed.

[0110] [Comparative Example 2]

[0111] The raw materials La2O3, SrCO3 and Fe2O3 were weighed in a molar ratio of 1:1:1 and mixed using a ball mill. The obtained powder was pelletized and heat treated at 1400°C for 10 hours to prepare an active material (La2SrFe2O7). A battery was prepared in the same manner as in Example 1 except that this active material was used.

[0112] [evaluate]

[0113] (XRD measurement)

[0114] The active materials obtained in Examples 1 to 6 were subjected to X-ray diffraction (XRD) measurement using CuKα rays. Figure 4 (a) shows the results of Example 1, Figure 4 (b) shows the results of Example 2, Figure 4 (c) The results of Examples 1 to 6 are summarized. Table 1 shows the positions of representative peaks obtained in each Example.

[0115] [Table 1]

[0116]

[0117] Here, it is known that CaFeO3 as a perovskite structure has characteristic peaks at 2θ=32.8°, 49.0°, 60.1°, and 70.2°, and it is known that SrFeO3 has characteristic peaks at 2θ=32.7°, 40.5°, 47.0°, and 58.6°. Figure 4 As shown in (a) and Table 1, characteristic peaks were observed at 2θ=32.4°, 35.2°, 46.5° and 59.7° for Example 1 (CaFeO2 (x=1)). Figure 4 (b) and Table 1 show that Example 2 (SrFeO2 (x = 0)) has characteristic peaks at 2θ = 31.6°, 34.1°, 45.4°, and 58.1°. Thus, the active material having an infinite layer structure has a peak at least at 2θ = 35.1° ± 1.0° that is not seen in the perovskite structure. Figure 4 (c) and Table 1 show that Examples 1 to 6 all have infinite layer structures.

[0118] (Charge and discharge test)

[0119] The batteries obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were subjected to charge and discharge tests in a chamber (cell) heated to 140°C. The conditions for the charge and discharge tests were -1.5V to 3.0V (vs. Pb / PbF2) and 0.03mA constant current charge and discharge. The results of Examples 1 to 6 are shown in Figure 5 (a), the results of Comparative Examples 1 and 2 are shown in Figure 5 (b), (c).

[0120] like Figure 5 As shown in (a), in the batteries of Examples 1 to 6, the charge and discharge capacities are all above 200 mAh / g. Figure 5 As shown in (b) and (c), in the batteries of Comparative Example 1 (SrFeO3) and Comparative Example 2 (La2SrFe2O7), the charge / discharge capacity did not reach 200 mAh / g. The batteries of Examples 1 to 6 had better capacity characteristics than those of Comparative Examples 1 and 2.

[0121] The results of comparing the discharge capacities (actually measured capacities) obtained in Examples 1 to 6 with the theoretical discharge capacities (theoretical capacities) per two-electron reaction are shown in FIG. Figure 6 Here, the atomic weight of Ca is smaller than that of Sr, so the theoretical capacity of CaFeO2 (x = 1) is better than that of SrFeO2 (x = 0). Figure 6 As shown in the theoretical capacity, it is predicted that the capacity increases linearly with the increase of x. Figure 6 As shown in the actual capacity, in the composition containing Sr at a predetermined ratio (0.6≤x<1), unexpectedly, the actual capacity increased significantly compared to the theoretical capacity, becoming equal to or higher than that of CaFeO2 (x=1). It is speculated that this is because CaFeO2 and SrFeO2, which have different spatial arrangements of elements, coexist at a predetermined ratio, resulting in deformation that allows fluoride ions to easily enter the active material.

[0122] [Example 7]

[0123] The raw materials La2O3 and NiO were weighed in a molar ratio of 1:2, and reacted in molten KOH at 400°C for 12 hours to obtain a precursor. The obtained precursor was granulated and vacuum sealed in a glass tube together with particles of a reducing agent (CaH2). The glass tube was sintered at about 300°C to synthesize an active material (LaNiO2). A battery was made in the same manner as in Example 1, except that the synthesized active material was used as the positive electrode active material.

[0124] [Example 8]

[0125] The raw materials CaCO3 and CuO were weighed in a molar ratio of 1:1 and mixed using a ball mill. The obtained powder particles were formed and calcined at 750°C in an oxygen atmosphere for 20 hours. After calcination, the particles were crushed, calcined again, and calcined again under the same conditions. The calcination and re-calcination were repeated 5 times to synthesize the active material (Ca0.828 A battery was prepared in the same manner as in Example 1 except that the synthesized active material was used as the positive electrode active material.

[0126] [evaluate]

[0127] (XRD measurement)

[0128] The active materials obtained in Examples 7 and 8 were subjected to X-ray diffraction (XRD) measurement using CuKα rays. Figure 7 (a) shows the results of Example 7, Figure 7 (b) shows the results of Example 8.

[0129] like Figure 7 As shown in (a), in Example 7 (LaNiO2), characteristic peaks were observed at 2θ=22.5°, 32.0°, 34.8°, 41.8°, 45.9°, and 58.9°, which are substantially the same as the peak positions observed in Example (SrFeO2).

[0130] On the other hand. Figure 7 (b) shows that in Example 8 (Ca 0.828 In the case of SrFeO2), characteristic peaks were observed at 2θ=16.7°, 28.2°, 32.9°, 33.9°, 36.0°, 43.6°, and 56.4°. This is a position slightly different from the peak position observed in Example (SrFeO2). It is speculated that this is because the composition slightly deviated from the CaCuO2 composition has a stable structure in which the CuO4 plane is deformed. In addition, the sample synthesized in Example 8 contains a small amount of CaO as a subphase.

[0131] (Charge and discharge test)

[0132] The batteries obtained in Examples 7 and 8 were subjected to charge and discharge tests in the same manner as in Examples 1 to 6 and Comparative Examples 1 and 2. Figure 8 (a) shows the results of Example 7, Figure 8 (b) shows the results of Example 8.

[0133] like Figure 8 As shown in (a), it was confirmed that the battery of Example 7 was the same as the batteries of Examples 1 to 6, and the charge and discharge capacity was above 200 mAh / h, showing high capacity. Specifically, although there was a small amount of irreversible capacity in the first cycle, a discharge capacity of about 360 mAh / g equivalent to about 3 electron reactions was confirmed in the second cycle. In addition, the active material of Example 8 is a material that has been deformed as an infinite layer structure, but as shown in FIG. Figure 8 As shown in (b), it was confirmed that the high capacity was exhibited.

Claims

1. A fluoride ion battery comprising a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and an electrolyte layer formed between the positive electrode layer and the negative electrode layer, in, The positive electrode active material or the negative electrode active material has an infinite layer structure and is composed of A p B q O r A crystalline phase represented by , wherein A is at least one of an alkaline earth metal element and a rare earth element, B is a transition metal element, p satisfies 0.8≤p≤1, q satisfies 0.8≤q≤1, and r satisfies 1.5≤r≤2.

5.

2. The fluoride ion battery according to claim 1, wherein: The ratio p / q of p to q is 1.

3. The fluoride ion battery according to claim 1, wherein: The ratio p / q of p to q is lower than 1.

4. The fluoride ion battery according to any one of claims 1 to 3, wherein The A is at least one of Ca, Sr, Ba, La and Ce.

5. The fluoride ion battery according to any one of claims 1 to 3, wherein The B is at least one of Fe, Ni and Cu.

6. The fluoride ion battery according to claim 5, wherein: The B is Fe.

7. The fluoride ion battery according to claim 1, wherein: The crystalline phase is composed of Ca x Sr 1-x FeO2 represents, wherein x satisfies 0<x<1.

8. The fluoride ion battery according to claim 7, wherein: The x satisfies 0.6≤x<1.

9. The fluoride ion battery according to claim 1, wherein: The crystalline phase is composed of Ca p CuO2 represents, wherein p satisfies 0.8≤p<1.

10. A fluoride ion battery comprising a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and an electrolyte layer formed between the positive electrode layer and the negative electrode layer, in, The positive electrode active material or the negative electrode active material has a crystalline phase having an infinite layer structure and containing A, B and O, wherein A is at least one of an alkaline earth metal element and a rare earth element, and B is a transition metal element. The crystalline phase has peaks at positions of 2θ=32.1°±1.0°, 2θ=35.1°±1.0°, 2θ=46.0°±1.0°, and 2θ=59.1°±1.0° in X-ray diffraction measurement using CuKα rays.

11. The fluoride ion battery according to claim 10, wherein: The A is at least one of Ca, Sr, Ba, La and Ce.

12. The fluoride ion battery according to claim 10 or 11, wherein: The B is at least one of Fe, Ni and Cu.

13. The fluoride ion battery according to claim 12, wherein: The B is Fe.

14. The fluoride ion battery according to claim 10, wherein: The crystalline phase is composed of Ca x Sr 1-x FeO2 represents, wherein x satisfies 0<x<1.

15. The fluoride ion battery according to claim 14, wherein: The x satisfies 0.6≤x<1.

16. A fluoride ion battery comprising a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and an electrolyte layer formed between the positive electrode layer and the negative electrode layer, in, The positive electrode active material or the negative electrode active material has a crystalline phase having an infinite layer structure and containing A, B and O, wherein A is at least one of an alkaline earth metal element and a rare earth element, and B is a transition metal element. The crystalline phase has peaks at 2θ=32.9°±1.0°, 2θ=36.0°±1.0°, 2θ=43.6°±1.0°, and 2θ=56.4°±1.0° in X-ray diffraction measurement using CuKα rays.

17. The fluoride ion battery according to claim 16, wherein: The A is at least one of Ca, Sr, Ba, La and Ce.

18. The fluoride ion battery according to claim 16 or 17, wherein: The B is at least one of Fe, Ni and Cu.

19. The fluoride ion battery according to claim 18, wherein: The B is Fe.

20. The fluoride ion battery according to claim 16, wherein: The crystalline phase is composed of Ca p CuO2 represents, wherein p satisfies 0.8≤p<1.

Citation Information

Patent Citations

  • Active material and fluoride ion battery

    JP2017143044A